Pendidikan Literasi di Era Teknologi dalam Mengatasi Kesenjangan Digital pada Maysarakat - Difa Salsabila Putri; Soelfema Soelfema; Lili Dasa Putri (BADAN PENERBIT STIEPARI PRESS, 2025)
Literacy has an important role in preparing for a person's future because through good literacy skills, they can understand, analyze, and use information effectively. In the midst of the continuous development of the digital era, information is now spreading rapidly and can be easily reached through the internet and social media. Therefore, literacy is becoming increasingly important in understanding the available information. This study uses a descriptive method with a survey approach, involving respondents from various backgrounds to understand their digital literacy level. The results show that despite the increased awareness of the importance of digital literacy, there is still a significant gap in individuals' ability to use technology effectively. Literacy education integrated with technology is expected to provide solutions to improve people's skills in facing digital challenges. In addition, this article also emphasizes the importance of collaboration between educational institutions, the government, and the private sector to create inclusive and sustainable education programs. Thus, it is hoped that people can be better prepared to face the digital era and utilize technology to improve their quality of life